Pembacaan kembali Traditionis Custodes Paus Fransiskus terhadap penggunaan Missale Romanum 1962. Sebuah tinjauan Liturgis-Eklesiologis dalam terang reformasi Konsili Vatikan II - Christianus Watu (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
Traditionis Custodes is an Apostolic letter issued by Pope Francis in the form of a Motu Proprio, i.e. on his own initiative. The content of this letter is about the use of the Roman Liturgy prior to the Reform of 1970. The main object of focus is the celebration of Mass with the Missale Romanum 1962. The Motu Proprio of the two previous Popes, John Paul II and Benedict XVI, permitted the use of the Missale Romanun 1962. The aim was to make room for those who were still attached to earlier forms of liturgical celebration. The implication is that the Missale Romanum 1962 is permitted as an extraordinary form of liturgical celebration, while the Missale Romanum 1970 is the ordinary or normal form. Pope Francis, through Traditionis Custodes, abrogated all the norms, instructions, consensus and customs of the previous Motu Proprio. He established the Missale Romanum 1970 as the only lex orandi (prayer order of the Church) of the Roman rite. This decision caused turmoil in the Church,especially strong criticism from users of the Missale Romanum 1962. This Motu Proprio was seen as a regression of the Church and a personal desire to abolish Church Tradition. Is this really the case? Why did Pope Francisabrogate the norms of the previous Motu Proprio? What is different about the 1962 and 1970 Missale Romanum? This article attempts to answer these questions with a liturgical-ecclesiological overview of the reforms of the Second Vatican Council.Key words: Ecclesial communion; liturgical reform; Traditionis Custodes; Summorum Pontificum; MissaleRomanum 1962.